Comparative study on growth performance of Thai Sharpunti (Puntius gonionotus) using two different weeds Duck weed (Lemna minor) and Azolla fern (Azolla pinneta) (Research in Agriculture Livestock and Fisheries, 2015)
The comparative growth performance study of Thai Sharpunti (Puntius gonionotus) was conducted from 20th March to 18th May, 2012by using duck weed (Lemna minor ) and Azolla fern (Azolla pinneta ) as in earthen pondof the Department of Aquaculture, Bangladesh Agricultural University, Mymensingh. Duck weed and Azolla fern were supplied as dietary feed in two separate treatments and each with three replications. Fifteen fingerlings of Thai sharputi was stocked in each pond. Average size and weight of Thai sarputi were 5.75 cm and 21g in T1 and 5.50 cm and20g in T2, respectively. The ranges of physico-chemical parameters viz, water temperature (25.00 to 33.500C), air temperature (31.00 to 34.500C), transparency (28 to 34 cm),dissolved oxygen (6.00 to 7.20 mg/l), free CO2 (2.00 to 3.33 mg/l), pH (6.9 to 7.45), total alkalinity (48 to 61 mg/l), phosphate-phosphorus (1.40 to 2.50 mg/l) and nitrate-nitrogen (2.13 to 3.20 mg/l) were within the productive range. Initial body weight, final body weight, weight gain, survival rate, specific growth rate(SGR), food convertion ratio (FCR), percent weight gain, average daily gain (ADG) were observed as21 and 20g, 356g and 308g, 335 and 288g, 90 and 85%, 558and 480% per day, 5.28 and 6.10, 1595 and 1440%, 5.58 and 4.80g in both the treatments,respectively. Calculated gross and net fish production in T1 with duck weed were 2.40 and 2.08 ton/ha/yr and in T2 with Azolla fern were 2.26 and 1.94 ton/ha/yr, respectively. It was found that the net fish production in T1 was 1.32 times higher than T2 (P?0.01, 0.05). The present study showed influence of duck weed as dietary feed on the production of Thai Sharpunti (P. gonionotus ) was positively significant. So it might be concluded that duckweed had better effect as dietary feed than Azolla fern on monoculture of Thai sharpunti.Res. Agric., Livest. Fish.2(2): 369-374, August 2015